Identification of isolate-specific proteins on sorbitol-enriched Plasmodium falciparum infected erythrocytes from Gambian patients. - Aley, S; Sherwood, J; Marsh, K; Eidelman, O; Howard, R (1986)
We have compared the surface radio-iodinated proteins of uninfected and Plasmodium falciparum-infected erythrocytes from natural infections of human patients. Cryopreserved infected blood from Gambian children with falciparum malaria was thawed, cultured to the middle trophozoite stage, and surface radio-iodinated. Trophozoite-infected cells were enriched about 10-fold on a Percoll gradient newly designed to separate cells based on their differential permeability to sorbitol. Infected blood was radio-iodinated and erythrocytes from the fraction enriched in parasitized cells and uninfected erythrocytes from the same sample obtained from the gradient and compared by SDS-PAGE and autoradiography. In each sample, parasitized erythrocytes contained one or more polypeptides of very high molecular weight (Mr 250 000-300 000) that were not found on uninfected erythrocytes from the same patient. These proteins were isolate-specific in size and number, suggesting that natural isolates contain a variable number of different P. falciparum phenotypes for this surface protein. In addition, these radio-iodinated surface proteins could not be extracted from the host cell membrane by the non-ionic detergent Triton X-100, but were extracted by SDS. The properties of these proteins suggest they are the equivalent for natural infections of the strain-dependent antigen previously described (Leech, Barnwell, Miller and Howard, 1984) on the surface of P. falciparum-infected Aotus erythrocytes. In addition, we observed a second parasite-dependent modification of labelled proteins on infected erythrocytes with the appearance of a new band of Mr 30 000. There were also variations in the pattern of radio-isotope labelled proteins on uninfected erythrocytes from different patients.